The Importance of Risk Stratification and Management of Newborn Babies of Women with a History of Graves' disease - Sze May Ng; Mark A Turner (International Journal of Clinical Endocrinology and Metabolism - Peertechz Publications, 2016)
Thyroid hormones are essential for normal brain development, growth and energy metabolism. During early pregnancy, the foetus is entirely dependent on maternal thyroid hormones and in the second and third trimesters, maternal thyroid hormones continue to provide sufficient thyroid hormones until birth. Maternal thyroid disease is common during pregnancy with hyperthyroidism during pregnancy occurring in 1% and autoimmune thyroiditis in 7% of pregnant women. Neonatal thyrotoxicosis may results from antibodies crossing from the mother to foetus and can result in serious adverse effects on the foetus. Management of thyrotoxicosis or hyperthyroidism during pregnancy is important because of the increased risk of miscarriage and preterm delivery and the potential damage to foetal neurodevelopment. It is therefore important to identify 'at risk' babies soon after birth according to the maternal history so that evaluation of maternal and neonatal thyroid status can be undertaken in a timely way. To date, there are no consensus guidelines as to how these babies should be managed and followed up within the United Kingdom. This may result in babies of women with a history of hyperthyroidism or Graves' having unnecessary blood tests and prolonged hospital stay after birth. A population-based survey in Sweden and a single-centre audit in Exeter, has shown that in fact very few babies with a maternal history of hyperthyroidism or Graves' disease develop thyroid disease and that too many thyroid function tests are unnecessarily being performed in newborn babies. This review aims to describe an approach to risk stratification and subsequent management of babies born to mothers with a history Graves' disease.